Green Purchase Intention Influenced by Attitude, Norms, Control, and Price Sensitivity as a Moderation - Khalisatuz Zahro; Gatot Nazir Ahmad; Nofriska Krissanya (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2025)
The purpose of this descriptive study is to identify the variables that affect a consumer's inclination to purchase eco-friendly personal care items: attitudes, subjective norms, perceived behavioral control, with the moderating variable price sensitivity. Primary data was gathered using a standardized questionnaire and disseminated as part of this quantitative study design to 322 respondents in Jakarta, Indonesia. The findings show that attitudes and subjective norms influence green purchase intention positively, while perceived control of behavior did not relate significantly. Further, it was observed that price sensitivity weakened the strength of relationships among attitude, subjective norms, and purchase intention. These results highlight both personal and social factors associated with sustainable consumption, but price sensitivity acts as the main barrier to eco-friendly purchasing decisions. In addition to offering insightful information for marketers and regulators looking to encourage consumers to make more sustainable decisions, this study deepens our understanding of consumer behavior in the beauty and personal care industry.